Liver resection for recurrent hepatocellular carcinoma after radiofrequency ablation therapy. Issue 4 (2nd January 2019) - Yamagishi, Shunsuke; Midorikawa, Yutaka; Nakayama, Hisashi; Higaki, Tokio; Moriguchi, Masamichi; Aramaki, Osamu; Yamazaki, Shintaro; Tsuji, Shingo; Takayama, Tadatoshi
Abstract : Aim: Although radiofrequency ablation (RFA) is an effective local treatment of hepatocellular carcinoma (HCC), local recurrence is relatively frequent. We aimed to elucidate the validity of salvage liver resection for recurrent HCC after RFA. Methods: Patients who underwent liver resection for recurrent HCC after RFA (LR after RFA) and those who underwent second liver resection for recurrent HCC (second LR) were included. The short‐term outcomes were compared between the two groups. The survival rates between the two groups were compared after propensity‐score matching to adjust for the variables, including patient background, liver function, and tumor status. Results: Major resection was frequently carried out in the LR after RFA group, but there was no significant difference both in operative data and complication rate between LR after RFA ( n  = 54) and second LR ( n  = 266) groups. After a median follow‐up period of 1.8 years (range, 0.2–10.5), the median overall survival was 4.4 years (95% confidence interval [CI], 2.2 – not applicable) and 5.6 years (95% CI, 4.5–7.3; P  = 0.023) in the LR after RFA group ( n  = 54) and second LR group ( n  = 54), respectively, and recurrence‐free survival was 1.3 years (0.4–2.2) and 1.2 years (0.5–1.8, P  = 0.469), respectively. The only independent factor for overall survival of the LR after RFA group was local recurrence (hazard ratio, 2.73; 1.06–9.00). Conclusions: Salvage liver resection of recurrent HCC after RFA could be recommended due to the safety of the procedure, especially in patients without local tumor progression after RFA.